Socio‐economic and demographic determinants of childhood anemia - Sankar Goswmai; Kishore K. Das (Brazilian Society of Pediatrics, 2015)
Objective: To evaluate socio‐economic and demographic determinants of anemia among Indian children aged 6 to 59 months. Methods: Statistical analysis was performed on the cross‐sectional weighted sample of 40,885 children from 2005‐2006 National Family Health Survey by using multinomial logistic regression to assess the significance of some risk factors in different degrees of child anemia. Anemia was diagnosed by World Health Organization (WHO) cut‐off points on hemoglobin level. Pearson's chi‐squared test was applied to justify the associations of anemia with different categories of the study population. Results: The prevalence of anemia was 69.5%; 26.2% mild, 40.4% moderate, and 2.9% severe anemia. Overall prevalence rate, along with mild and moderate cases, showed an increasing trend up to 2 years of age and then decreased. Rural children had a higher prevalence rate. Of 28 Indian states in the study, ten states showed very high prevalence, the highest being Bihar (77.9%). Higher birth order, high index of poverty, low level of maternal education, mother's anemia, non‐intake of iron supplements during pregnancy, and vegetarian mother increased the risks of all types of anemia among children (p < 0.05). Christian population was at lower risk; and Scheduled Caste, Scheduled Tribe, and Other Backward Class categories were at higher risk of anemia. Conclusion: The results suggest a need for proper planning and implementation of preventive measures to combat child anemia. Economically under‐privileged groups, maternal nutrition and education, and birth control measures should be priorities in the programs.